Pengaruh Knowledge Hiding, Psychological Distress, Psychological Stress terhadap Job Performance Pegawai RSJ - Denny Styvan's Dion; Netania Emilisa; Febby Laddyana Citra (Penerbit Goodwood, 2022)
Purpose: This study aims to analyze Knowledge Hiding (KH), Psychological Distress (PD), Psychological Stress (PS) on Employees at Mutiara Sukma Mental Hospital NTB. Research Methodology: The sample used was purposive sampling to 125 employees of RSJ Mutiara Sukma NTB by distributing online questionnaires. Using the Multiple Linear Regression Analysis method with SPSS version 23 program. Result: The results showed that KH had no effect on Job Performance (JP), PD had a positive effect on JP, while PS had a negative effect on JP. Limitation: This research was only carried out at Mutiara Sukma Hospital, NTB, so it cannot represent organizations engaged in other fields. The variables in this study contain KH, PD, PS, to see their effect on Job Performance. ContributionResearchers hope this research is able to provide an overview to management about the conditions that occur in the organization, and hopes to provide views on managing, and maintaining a healthy work environment so that it can affect the performance of members. Researchers found different results with previous studies. In this study, PD has a positive effect on JP, and KH has no effect on JP.